THE IMPACT OF FARMER GROUP MEMBERSHIP ON REVENUES, COSTS, AND INCOME GENERATED FROM CAYENNE PEPPER FARMING IN INDONESIA - Hardja, Adiva Fitri Khalishah Tjiptara; Harmini, Harmini; Muflikh, Yanti Nuraeni (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Cayenne pepper, a national strategic commodity, has fluctuating prices and production risks. As a result, the income of cayenne pepper farmers fluctuates. Farmer groups that function as learning classes, work platforms, and production units for farmers make few of the many efforts to deal with this issue. This study aims to (1) analyze the revenue, cost structure, and income of cayenne pepper farming among farmer group members and non-farmer group members in Indonesia, and (2) analyze the impact of farmer group membership on revenue and cost structure, and cayenne pepper farming income. The data used were secondary data from the 2014 Horticultural Crop Household Survey, with a total of 18.049 households. Data processing was performed qualitatively and quantitatively. Qualitative data analysis was performed using descriptive and quantitative methods using propensity score matching (PSM). The study results showed that farmers who are farmer group members have higher revenues, costs, and incomes than farmers who are not. Farmer groups membership impact on higher costs as well as significant positive effect towards farmer’s revenueion and income.